Ships, Ports, and the Sea as Colonial Infrastructure: Hydrocolonialism in Iksaka Banu’s Semua Untuk Hindia - Ferdiansyah, Rafi; Khasanah, Siti Uswatun (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2026)
This article examines two short stories by Iksaka Banu, Pollux and Penabur Benih from Semua untuk Hindia (2014) through the framework of hydrocolonialism. Departing from previous studies that have largely framed colonialism in Iksaka Banu’s works as issues of subject ambivalence, hegemony, resistance, or traumatic memory, this article shifts the focus to how colonial power operates through the sea, ports, ships, mobility, and navigational knowledge. Using the method of close reading, the analysis focuses on textual units such as detention, deportation, embarkation, exile, burial at sea, trade-mission conflicts, signaling systems, maps, and the naming of land. The analysis reveals that Pollux portrays colonialism as a process of the flow of bodies from land to sea: the bodies of detainees are classified at the Stadhuis, their visibility is regulated at Sunda Kelapa Port, and they are then transported to the periphery via the corvette Pollux. Meanwhile, Penabur Benih depicts colonialism from the sea to the land: the sea becomes a space of disposal that normalizes death, the Duyfken ship functions as a trade-religious micro colony, while maps, signal flags, and the naming of Enggano bring the land into the colonial regime of knowledge before the landing takes place. Thus, this article argues that the sea, the port, and the ships in these two short stories are not merely maritime settings, but narrative infrastructures as well as infrastructures of power that regulate the body, mobility, visibility, disposal, and the authority of knowledge. The contribution of this article lies in a specific reading of Pollux and Penabur Benih as texts that reveal colonialism not merely as territorial occupation, but as material-spatial governance through water.